The Assassination Of Lord Mayo: The 'first' Jihad? - James, Helen (Penerbit Universiti Sains Malaysia (USM Press), 2009)
In February 1872, Lord Mayo, Governor-General of India, was assassinated at the penal settlement of Port Blair in the Andaman Islands whilst paying a viceregal visit to the Province of British Burma. His assassin, a Pathan from North West India who had been in the Peshawar police, made no attempt to escape. He had been serving a life sentence for murder, a murder of which he had declared himself 'Not Guilty'. The manuscripts and papers relating to the thorough investigation that was immediately launched into the death of the Viceroy use the word jihad ('struggle for the Faith') to explain the motivation for the assassination. However, intriguing unanswered questions remain that this paper will attempt to highlight. Was the alleged assassin a mere tool in a larger game of world politics? Was Lord Mayo's security detail deliberately slack in performing its duties? Based on the manuscript collections in the Cambridge University Library, this paper scrutinises the evidence and frames it within the colonial history of the loss of Burmese independence in three wars with Britain from 1824 to 1885.